Human resources for health strategies adopted by providers in resource-limited settings to sustain long-term delivery of ART: a mixed-methods study from Uganda - Zakumumpa, Henry (Hum Resour Health, 2016)
BACKGROUND: Human resources for health (HRH) constraints are a major barrier to the sustainability of antiretroviral therapy (ART) scale-up programs in Sub-Saharan Africa. Many prior approaches to HRH constraints have taken a top-down trend of generalized global strategies and policy guidelines. The objective of the study was to examine the human resources for health strategies adopted by front-line providers in Uganda to sustain ART delivery beyond the initial ART scale-up phase between 2004 and 2009. METHODS: A two-phase mixed-methods approach was adopted. In the first phase, a survey of a nationally representative sample of health facilities (n = 195) across Uganda was conducted. The second phase involved in-depth interviews (n = 36) with ART clinic managers and staff of 6 of the 195 health facilities purposively selected from the first study phase. Quantitative data was analysed based on descriptive statistics, and qualitative data was analysed by coding and thematic analysis. RESULTS: The identified strategies were categorized into five themes: (1) providing monetary and non-monetary incentives to health workers on busy ART clinic days; (2) workload reduction through spacing ART clinic appointments; (3) adopting training workshops in ART management as a motivation strategy for health workers; (4) adopting non-physician-centred staffing models; and (5) devising ART program leadership styles that enhanced health worker commitment. CONCLUSIONS: Facility-level strategies for responding to HRH constraints are feasible and can contribute to efforts to increase country ownership of HIV programs in resource-limited settings. Consideration of the human resources for health strategies identified in the study by ART program planners and managers could enhance the long-term sustainment of ART programs by providers in resource-limited settings.